PENGARUH PROMOSI, HARGA DAN KUALITAS TERHADAP KEPUTUSAN PEMBELIAN ANDROID SAMSUNG DI KOTA SEMARANG - Ghoini, Sofi Nurul; Rodhiyah, Rodhiyah; Ngatno, Ngatno (Jurnal Ilmu Administrasi Bisnis, 2016)
The increasing of technology development to be more sophisticated and also the rising of market competitions to be fierce make Samsung Corporation should be more content in showing its benefit products, especially for Android, in order to grab consumers concern. The problem is the content product of Samsung Android become more competitive.This study aims to test the effects of promotion, price, and quality to Samsung Android purchasing decision partially and simultaneously. It is an explanatory research with 100 respondents around Semarang city as its samples by using purposive sampling method (based on certain conditions) and also using questionnaires as research instrument and doing some interviews as data collecting method. This research uses some data analytical methods, such as validity test, reliability test, correlation test, coefficient of determination test, simple linear regression, multiple linear regression, t-test, and F-test, which are supported by SPSS 15.00.The categorization of promotion is good and the mean variabel score is 3,51. T-test value is 4,489 > t-table 1,9845. The corellation between promotion and purchasing decision is intermediate. The regression coefficient of promotion is 0,316 and its coefficient of determination is 17,1%. The categorization of price is good enough and the mean variabel score is 3,41. T-test value is 5,081 > t-table 1,9845. The corellation between price and purchasing decision is intermediate. The regression coefficient of price is 0,442 and its coefficient of determination is 20,9%. The categorization of quality is good and the mean variabel score is 3,72. T-test value is 5,410 > t-table 1,9845. The corellation between quality and purchasing decision is intermediate. The regression coefficient of quality is 0,524 and its coefficient of determination is 23%. The categorization of purchasing decision is good enough and the mean variabel score is 3,34.The results conclude that promotion, price, and quality have influences to Samsung Android purchasing decision in partial and simultant. The recommendations for the company are like Samsung Corporation should defend the promotion to be more interesting and increase the quantity of advertisement and publicity, make the prices competitive based on quality, increase the product quality. For the consumers, they should choose Android product based on their needs, not only for their want. Select the product corectly based on quality in order that it can’t be broken easily.